The Relationships Between Vitamin K and Cognition: A Review of Current Evidence - Alisi, Ludovico; Cao, Roberta; De Angelis, Cristina; Cafolla, Arturo; Caramia, Francesca; Cartocci, Gaia; Librando, Aloisa; Fiorelli, Marco (Frontiers in Neurology, 2019)
Vitamin K is a fat-soluble nutrient discovered in 1935 and its role in blood coagulation has been thoroughly explored. In recent years, studies conducted in vitro and on animals highlighted vitamin K involvement in brain cells development and survival. In particular, vitamin K seems to have an antiapoptotic and anti-inflammatory effect mediated by the activation of Growth Arrest Specific Gene 6 and Protein S. Moreover, this vitamin is involved in sphingolipids metabolism, a class of lipids that participate in the proliferation, differentiation and survival of brain cells. An altered expression in sphingolipids profile has been related to neuroinflammation and neurodegeneration. This review stems from a growing interest in the role of vitamin K in brain functions, especially in cognition, also in view of an expected increase of prevalence of Alzheimer’s disease and other forms of dementia. It collects recent researches that show interesting, even though not definitive, evidence of a direct correlation between vitamin K levels and cognitive performance. Moreover, vitamin K antagonists, used worldwide as oral anticoagulants, according to recent studies may have a negative influence on cognitive domains such as visual memory, verbal fluency and brain volume. The aim of this review is to analyze the evidence of clinical studies carried out up to date on the relationship between vitamin K intake and cognitive performances. The involvement of vitamin K antagonists (VKAs) in declining cognitive performances is also addressed separately.